Steroids Significantly Decrease Postoperative Postural Hypotension in Total Knee Replacement - Cheng, Gloria H. M.; Tan, Gabriel K. Y.; Kamarudin, Muhammad F. B.; Lee, Bryan W. W.; Mei, Yap Yan; Tan, Kelvin G. (The Journal of Knee Surgery, 2021)
Total knee replacement (TKR) is one of the most common orthopaedic procedures performed, and enhanced recovery after surgery (ERAS) has been developed and incorporated into inpatient surgical pathways to improve patient outcomes. Under ERAS recommendations, multimodal prophylaxis has been used to help manage postoperative nausea and vomiting (PONV) following TKR. Dexamethasone is one of the commonly used for this and the anti-inflammatory properties could depress vagal activity, reducing postural hypotension (PH). The hypothesis of this study is that postoperative dexamethasone use is associated with lower rates of early postoperative PH following TKR surgery. In our institution, patients who undergo elective primary TKR are admitted on the day of surgery and follow a standardized ERAS protocol. Data on patients who underwent elective primary TKR under a single adult reconstruction team from September 2017 to March 2020 were reviewed and analyzed. A review of demographic characteristics, surgical data, postoperative medications, and postoperative notes was performed. Binary logistic regression was used to assess the effect of the use of dexamethasone on PH, with an adjusted odds ratio (OR) calculated after accounting for potential confounders. Of the 149 patients were included in the study, 78 had dexamethasone postoperatively, and 71 did not. Patients who had received dexamethasone were statistically less likely to suffer from PH (OR = 0.31, p = 0.03) and less likely to develop PONV (OR = 0.21, p = 0.006). Patients who had received dexamethasone were more likely able to participate in early physiotherapy (OR = 2.42, p = 0.14), and this result was statistically insignificant. The use of postoperative intravenous dexamethasone is significantly associated with lower rates of postoperative PH after TKR. However, more studies are required to assess the optimal dosing amount and frequency, as well as to assess other factors which can enhance early postoperative patient mobilization as part of our goals for ERAS. This therapeutic study reflects level of evidence III.
Keywords: total knee replacement; dexamethasone; postural hypotension